Reductive immobilization of uranium by stabilized zero-valent iron nanoparticles: Effects of stabilizers, water chemistry and long-term stability - Zhao, Xiao; Liu, Wen; Cai, Zhengqing; Fu, Jie; Duan, Jun; Zhao, Dongye; Michael Bozack; Yucheng Feng (Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2020)
Uranium is one of the most commonly detected radionuclides in the environment. Of the two most predominant oxidation states, U(VI) is much more soluble, mobile and toxic than U(IV). Consequently, converting U(VI) to U(IV) can facilitate the removal of U from water and reduce its mobility and biological exposure. In this work, stabilized zero-valent iron (ZVI) nanoparticles were prepared using starch or carboxymethyl cellulose (CMC) as stabilizers and then tested for reductive removal of U(VI) from simulated groundwater. Nearly 100% removal of U(VI) (initial U = 25 mg/L) was achieved using CMC-stabilized ZVI (Fe = 35 mg/L) at pH 6. In pH range of 6–9, the lower pH favored the reaction. CMC-ZVI nanoparticles presented better deliverability than starch-ZVI, while bare ZVI nanoparticles was almost trapped in the soil column. CMC-ZVI worked effectively in the presence of a model humic acid (up to 10 mg/L as TOC) and bicarbonate (1 mM), though higher dosages of the ligands inhibited U(VI) removal. After treatment, no re-mobilization of U was detected when aged for 6 months under anoxic conditions and the addition of strong ligands only remobilized U(VI). When exposed to oxic conditions, the immobilized U will be partially oxidized and remobilized due to the ingress of atmospheric O2 and CO2. In terms of toxicity reduction, the ZVI treated U had almost no inhibition for natural bacteria activity, while dissolved U(VI) showed significant inhibitive effects. The CMC-ZVI nanoparticles may serve as effective reactive materials to facilitate immobilization of U(VI) in groundwater, which in turn can greatly mitigate the human exposure and toxic effects of U on biota.
Keywords: Radionuclide; Reductive immobilization; Stabilized nanoparticle; Uranium immobilization; Zero valent iron